A 3D printed bullet‐shaped filter based on zero‐gap circular waveguide cavities. Issue 12 (19th October 2022) - Shu, Minjie; Wu, Wenxuan; Liang, Ruihua; Shang, Xiaobang; Guo, Cheng; Zhang, Anxue
Abstract: This paper presents an improved zero‐gap waveguide structure with convex‐shaped gap waveguide pins and zero height air gap, which is used to enhance the structural strength and reduce the assembly errors due to the air gap variation. A fourth‐order bullet‐shaped circular waveguide filter is designed and fabricated to validate the proposed structure. To ease the 3D printing difficulty of the designed filter, the cosine‐shaped top is utilized for self‐supporting. Besides, a metallic ridge between adjacent cavities is introduced to enhance the electric coupling. The metallic ridge as well as the slots at the bottom plate help to increase the stopband suppression. Finally, the measured results of the fabricated filter excited with coaxial connectors match well with the simulation.